Do the dietary ingredients of low-protein formulated diet provide a sufficient selenium source in Australian snapper Pagrus auratus diet (Bloch & Schneider 1801)?. - Pham, H.; Fotedar, Ravi (Elsevier BV, 2017)
A 10-week feeding trial was conducted to evaluate the necessity of supplementing selenium(Se) in a low-protein basal diet for Australian snapper Pagrus auratus, a slower-growing fishspecies. Dietary Se supplementation was tested against commercial barramundi diet, mostcommonly fed to Australian snapper. Se-yeast was added to a reconstituted commercialdiet and to a formulated basal diet at 0, 0.8 and 1.0 mg/kg Se to form six isoenergetic testdiets to evaluate the effects of diet types, dietary Se supplementation and their interactionon the growth, feed utilisation, body composition and liver morphology of juvenile Aus-tralian snapper. These Se supplementation levels resulted in total dietary Se levels of 0.92,1.68, 1.76, 1.67, 2.59 and 2.77 mg/kg, respectively. Each test diet was fed to triplicate groupsof Australian snapper in a flow-through seawater system. There were no significant inter-action between diet types and Se supplementation on all tested parameters of the snapper.Regardless of the diet types, snapper fed 1.0 mg/kg Se-supplemented diet attained signif-icantly lower growth rate than the fish fed diets supplemented with 0 and 0.8 mg/kg ofSe. Feed conversion ratio was significantly increased in snapper fed diets supplementedwith 1.0 mg/kg Se. There were no effects of both diet types and Se supplementation onthe proximate composition of the muscle and whole-body except the reduced moistureand gross energy levels in the whole-body of snapper fed 1.0 mg/kg Se-supplemented diet.The Se contents in the muscle and liver tissues showed positive linear relationships withdietary Se levels. Fish fed diet supplemented with 1.0 mg/kg Se showed increased hepaticlipid compared with the fish fed 0 and 0.8 mg/kg Se-supplemented diets. Histopathologicalalterations were observed in liver tissues of snapper fed the basal diet containing 2.77 mg/kgSe. The results concluded that the protein and Se requirements of Australian snapper arelow and can be met by lower protein ingredients with the endogenous Se. Further, thedietary Se threshold level in Australian snapper fed a basal diet was 2.77 mg/kg, whereasthis level was only 1.76 mg/kg in the reconstituted commercial diet.